A proposed program for the correction of promiscuous micturition among students in the secondary schools, Division of City Schools, Manila - Olivares, Victorina A. 1925- (s.n.], 1971)
School facilities and a healthful environment influence the development of health practices among the youth. The study proposed a program for the correction of promiscuous micturition among students of the public secondary schools in Manila. The normative survey method of research was used in this study. Information sought in the survey included the personal data of the students, the micturition practices and their attitudes toward micturition practices in public places, and the measures to correct promiscuous micturition as suggested by the students. A proposed program included three phases: (1) Health Instruction, (2) Healthful Living, and (3) Health Services.